2022
DOI: 10.17977/um009v31i22022p078
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Buku Ajar Berbasis Augmented Reality (Ar) Menggunakan Assemblr Apps Pada Tema 9 “Menjelajah Angkasa Luar” Kelas Vi Sekolah Dasar

Abstract: This study aims to determine the results of the validity and effectiveness of the textbooks. The research used is the research and development research of the Borg and Gall model with 10 stages of research, namely preliminary research, planning and development, initial product design development, product validation, initial product revision, use trials, product development revisions, effectiveness trials, final product, dissemination. The results of data analysis for sixth grade students at SDN 1 Grajagan, SDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Apriliani [35] found that the use of AR as a learning medium can improve student learning outcomes. This is similar to the research conducted by Santi et al [31] who found that AR-based textbooks can improve student learning outcomes. The use of AR in learning about the solar system in primary school can also improve students' critical thinking skills [37], [38].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Apriliani [35] found that the use of AR as a learning medium can improve student learning outcomes. This is similar to the research conducted by Santi et al [31] who found that AR-based textbooks can improve student learning outcomes. The use of AR in learning about the solar system in primary school can also improve students' critical thinking skills [37], [38].…”
Section: Resultssupporting
confidence: 90%
“…Another tool used to develop AR in solar system education is Assemblr apps. This tool was used by Santi, et al [31] in a study aimed at developing AR-based textbooks. Assemblr…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Siahaan, et al 2019). 2) Research by (Isnawati Amir, 2017) on the development of textbooks and Augmented Reality on the concept of high school storytelling with an average score of 4.3 valid categories of 2 validators and the average prescription of teacher response scores of 4.4 (good category) (Isnawati, 2017). 3) Research by (Daniel Indrayana, 2019& Fatwatush, 2019 on the design of a web-based SOLE (Self Organized Learning Environment) learning system with VAK learning styles to improve cognitive understanding of students who get a student response percentage of 86.09% which is in the "Very Good" category (Daniel, 2019).…”
Section: % Disagreementioning
confidence: 99%